Identifying the Structure and Propagation of Dawnside Pc5 ULF Waves Using Space‐Ground Conjunctions. Issue 12 (21st December 2022) - Zhang, W.; Nishimura, Y.; Wang, B.; Hwang, K.‐J.; Hartinger, M. D.; Donovan, E. F.; Angelopoulos, V.; Hampton, D.
Abstract: Pc5 ultralow frequency waves are important for transferring energy between the magnetosphere and ionosphere. While many observations have been performed on Pc5 waves properties, it has been difficult to determine the source region, signal propagation path, and the two‐dimensional structure of Pc5 waves beyond coverage by a small number of satellites. Pc5 waves often show a dawn‐dusk asymmetry, but the cause of the asymmetry is under debate. To address these issues, we used conjunction events between the THEMIS satellites and all‐sky imagers and analyzed two Pc5 wave events that were stronger on the dawnside. For both events, the Pc5 waves propagated from dawnside magnetopause toward the nightside magnetosphere. The Pc5 waves were also associated with dawnside magnetopause surface waves, which were probably induced by the Kelvin‐Helmholtz instability. The ionospheric equivalent currents identified multiple vortices on the dawnside associated with quasi‐periodic auroral arcs and much weaker perturbations on the duskside. Global auroral imaging also presented a similar dawn‐dusk asymmetry with multiple arcs on the dawnside, while only one or two major arcs existed on the duskside. Pc5 waves in the magnetosphere had an anti‐phase relation between the total magnetic field and thermal pressure, with a slower propagation velocity compared with magnetohydrodynamic waves. The Poynting flux was anti‐sunward with an oscillating field‐aligned component. These properties suggest that Pc5 waves were slow or drift mirror mode waves coupled with standing Alfven waves. The ground‐based and multi‐satellite observations provide crucial information for determining the Pc5 waves properties, possible source region, and signal propagation path. Plain Language Summary: Pc5 ultralow frequency waves (1.66–6.66 mHz) are large‐scale waves in space, and Pc5 waves are capable of interacting with particles and modulating higher frequency waves, resulting in energy transfer in the magnetosphere‐ionosphere system. However, it is difficult to find the exact signal propagation path and identify the source due to the limited sparse satellite observations in space. We investigated two Pc5 wave events by using the conjunctions of ground magnetometers, all‐sky imagers, and Time History of Events and Macroscale Interaction During Substorms (THEMIS) satellites. We found that the aurora shows periodic intensification and the ionospheric currents had multiple vortices with dawn‐dusk asymmetry. The Pc5 waves in the magnetosphere are identified as standing waves that were coupled with surface waves at the magnetopause traveling anti‐sunward. We suggest that magnetopause surface waves were induced by Kelvin‐Helmholtz instability and drive the Pc5 waves. The dawn‐dusk asymmetry of Kelvin‐Helmholtz instability in the magnetosheath may explain the current asymmetric pattern in the ionosphere. Key Points: Two Pc5 wave events we analyzed were highly dawn‐dusk asymmetric, with stronger magnetic field perturbations on the dawnside than duskside Slow or drift mirror mode waves coupled with standing Alfven waves in the magnetosphere were driven by the magnetopause surface waves Surface waves by Kelvin‐Helmholtz instability along the magnetopause is suggested to be the source of the dawnside Pc5 waves